Red cell distribution width (RDW) as a predictor of cardiovascular outcomes in extensive aortoiliac disease - Nuno Rafael Vieira Cardoso (2022)
Background: Aortoiliac peripheral artery disease may lead to disabling lower limb claudication or to lower limb chronic threatening ischemia, which is associated with increased short and long-term morbi-mortality. The red blood cell distribution width-coefficient of variation (RDW-CV) has been able to predict outcomes in other atherosclerotic diseases, such as myocardial infarction and stroke. The main objective of this study was to assess the predictive ability of perioperative RDW-CV in accurately predicting short and long-term major adverse cardiovascular events (MACE) and all-cause mortality in patients submitted to aortoiliac revascularization due to extensive aortoiliac atherosclerotic disease. Methods: From 2013 to 2020, patients who underwent aortoiliac revascularization due to severe aortoiliac disease were included in a prospective cohort. Blood samples were taken preoperatively and the patient's demographics, comorbidities, and postoperative outcomes were assessed. A multivariate Cox regression model was used to adjust for confounding and assess the independent effect of these prognostic factors on the outcomes. Results: The study group included 107 patients. Median follow-up was 57 (95% CI 34.4-69.6) months. Preoperative RDW-CV was increased in thirty-eight patients (35.5%). Increased RDW-CV was associated with congestive heart failure - adjusted odds ratio of 5.043 (95% CI 1.436-17.717, p=0.012). It could predict long-term occurrence of MACE (adjusted hazard ratio, aHR=1.065, 95% CI 1.014-1.118, p=0.011), all-cause mortality (aHR=1.069, 95% CI 1.014-1.126, p=0.013), acute heart failure (AHF) (aHR=1.569, 95% CI 1.179-2.088, p=0.002), and stroke (aHR=1.343, 95% CI 1.044-1.727, p=0.022). Conclusions: RDW-CV is a widely available and low-cost marker that was able to independently predict long-term AHF, stroke, MACE, and all-cause mortality in patients with extensive aortoiliac disease submitted to revascularization. This biomarker could help assess which patients would likely benefit from stricter follow-up in the long-term.